PENGARUH KONFLIK PEKERJAAN-KELUARGA TERHADAP NIATAN KELUAR DAN KINERJA KARYAWAN MELALUI KETERIKATAN KERJA SEBAGAI VARIABEL MEDIASI (Studi pada Pegawai ASN Soerojo Hospital Magelang) - Nurrahmawati, Choirisa; Yuniawan, Ahyar (Diponegoro Journal of Management, 2024)
ABSTRACT There have been several demographic changes that society has experienced in recent years with the entry of women into the labor market. As a result, there is a possibility of a mismatch between work and family. In this case, it is not only women who have families, but men too. The population in this study were ASN Employees at Soerojo Hospital Magelang. The sampling technique in this research uses the Proportionate Stratified Random Sampling technique. The analysis technique used is path analysis with the SPSS 26 program to determine the path coefficient and the influence of the independent variable on the dependent variable through the mediating variable. This research aims to analyze the impact of Work-Family Conflict on Turnover Intention and Individual Performance which is mediated by Work Engagement in Soerojo Hospital. The research results show that the higher the Work-Family Conflict, the higher the Turnover Intention, conversely, the higher the Work-Family Conflict, the lower the Individual Performance. Work Engagement is able to mediate the impact of Work-Family Conflict on Turnover Intention and decreasing Individual Performance. Soerojo Hospital can carry out more in-depth evaluations of employees through surveys and counseling related to problems faced by employees such as work-family conflict. This can help employees to resolve their problems, understand what is needed, and also understand what happens to employees as a result of work-family conflict to prevent increased turnover intentions and decreased individual performance.